2021
DOI: 10.1002/mp.15260
|View full text |Cite
|
Sign up to set email alerts
|

Automatic segmentation of organs‐at‐risks of nasopharynx cancer and lung cancer by cross‐layer attention fusion network with TELD‐Loss

Abstract: Purpose: Radiotherapy is one of the main treatments of nasopharyngeal cancer (NPC) and lung cancer. Accurate segmentation of organs at risks (OARs) in CT images is a key step in radiotherapy planning for NPC and lung cancer. However, the segmentation of OARs is influenced by the highly imbalanced size of organs, which often results in very poor segmentation results for small and difficult-to-segment organs. In addition, the complex morphological changes and fuzzy boundaries of OARs also pose great challenges t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…A specific study on small OARs was performed by Liu et al for nasopharyngeal tumors [ 31 ]. The authors validated their model against other state-of-the-art networks on the public StructSeg 2019 challenge dataset, reporting an average DSC = 0.80.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A specific study on small OARs was performed by Liu et al for nasopharyngeal tumors [ 31 ]. The authors validated their model against other state-of-the-art networks on the public StructSeg 2019 challenge dataset, reporting an average DSC = 0.80.…”
Section: Resultsmentioning
confidence: 99%
“…The current availability of public datasets and scientific challenges, such as the HECKTOR challenge [61], the StructSeg challenge (https://structseg2019.grand-challenge.org (accessed on 4 May 2023)), and the TCGA-HNSC dataset [62], provides an excellent opportunity to benchmark and compare methods. If these datasets and challenges are widely adopted by researchers, as carried out in [18,31], it would be possible to reach higher standards of evidence.…”
Section: Future Prospectivementioning
confidence: 99%
“…Liu et al. ( 24 ) proposed a loss function called TELD-loss for automatic segmentation of the OARs for nasopharyngeal and lung cancer, and the results showed that the mean DSC values of the temporal lobes on the left and right side were 0.7873 and 0.5969, respectively. Compared with them, the resultant value in this study was 0.88, which has a sufficient improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder DSC of 0.94 and eye DSC of 0.91 were reported by Zhou et al 14 The OARs with small volumes and fuzzy boundaries, such as optic chiasma, pose challenges to the segmentation task. To deal with this problem, researchers tried to find solutions by improving their network architecture designs 16 or loss functions. 16 A cross-layer spatial attention map fusion architecture 16 was proposed to enhance the network’s attention to the target area.…”
Section: Organ and Lesion Segmentationmentioning
confidence: 99%